2023
DOI: 10.1007/s10557-023-07434-3
|View full text |Cite
|
Sign up to set email alerts
|

Acute Biomechanical Effects of Empagliflozin on Living Isolated Human Heart Failure Myocardium

Abstract: Purpose Multiple randomized controlled trials have presented SGLT2 inhibitors (SGLT2i) as novel pharmacological therapy for patients with heart failure, resulting in reductions in hospitalization for heart failure and mortality. Given the absence of SGLT2 receptors in the heart, mechanisms of direct cardioprotective effects of SGLT2i are complex and remain to be investigated. In this study, we evaluated the direct biomechanical effects of SGLT2i empagliflozin on isolated myocardium from end-stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…More knowledge is needed to elucidate whether this single increase in Tau logistic depicts a potential worsening of diastolic function at this disease stage. Accordingly, the diuretic effect may explain some of the RV effects seen in present study, but we cannot exclude other mechanisms might play a role, as recent studies describe a direct cardiac effect of empagliflozin on cardio myocytes and SGLT2-knock out mice without affecting systemic SGLT2 function (36)(37)(38). Either way, we solely see a slight disease reduction and not a normalization of RV function in present study, emphasizing the need for further investigation of empagliflozin's role as a potentially new therapy complimenting current RV failure management.…”
Section: The Effects Of Empagliflozin Treatment On Rv Functionmentioning
confidence: 77%
“…More knowledge is needed to elucidate whether this single increase in Tau logistic depicts a potential worsening of diastolic function at this disease stage. Accordingly, the diuretic effect may explain some of the RV effects seen in present study, but we cannot exclude other mechanisms might play a role, as recent studies describe a direct cardiac effect of empagliflozin on cardio myocytes and SGLT2-knock out mice without affecting systemic SGLT2 function (36)(37)(38). Either way, we solely see a slight disease reduction and not a normalization of RV function in present study, emphasizing the need for further investigation of empagliflozin's role as a potentially new therapy complimenting current RV failure management.…”
Section: The Effects Of Empagliflozin Treatment On Rv Functionmentioning
confidence: 77%
“…Thus, the beneficial effects of empagliflozin on the heart are unlikely to involve angiotensin. Yet, importantly, SGLT2 expression in the heart is absent [6,32], and thus any local cardiac effect of empagliflozin must be due to an off-target effect. Indeed, empagliflozin did improve contraction and relaxation kinetics in human left ventricular tissue slices, and reduced infarct size in the isolated Langendorff-perfused mouse heart exposed to 30 min of global ischemia [6,32].…”
Section: Discussionmentioning
confidence: 99%
“…Yet, importantly, SGLT2 expression in the heart is absent [6,32], and thus any local cardiac effect of empagliflozin must be due to an off-target effect. Indeed, empagliflozin did improve contraction and relaxation kinetics in human left ventricular tissue slices, and reduced infarct size in the isolated Langendorff-perfused mouse heart exposed to 30 min of global ischemia [6,32]. It has also been shown to suppress inflammation and sympathetic activity in the rat heart [33].…”
Section: Discussionmentioning
confidence: 99%
“…In view of a lack of effect of OM on intracellular Ca-transients, the functional significance of this change is not clear. Moreover, tests of effects of OM in living tissue slices from human HF patients showed that although there was an increase in contractility and duration of contraction time, relaxation was impaired [103]. The relaxation prolongation worsened with increased beating rates and was suggested to possibly promote arrhythmias.…”
Section: Myosin Heavy Chain As a Drug Targetmentioning
confidence: 99%